2013
DOI: 10.1371/journal.pone.0076463
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Breast Cancer in the Japanese Population

Abstract: Breast cancer is the most common malignancy among women in worldwide including Japan. Several studies have identified common genetic variants to be associated with the risk of breast cancer. Due to the complex linkage disequilibrium structure and various environmental exposures in different populations, it is essential to identify variants associated with breast cancer in each population, which subsequently facilitate the better understanding of mammary carcinogenesis. In this study, we conducted a genome-wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 45 publications
3
37
1
1
Order By: Relevance
“…Our FGFR2 SNP, rs2981579, was first identified by Thomas et al [31] and independently replicated in two other GWAS [23, 32]. Other GWAS found stronger associations with other SNPs in the same gene [1, 7, 8, 10, 12, 15, 19, 22, 26]. Ahsan et al [1], for example, reported genome-wide significant p-values for 4 FGFR2 SNPs and young-onset breast cancer, with the smallest p-value seen for rs2981579.…”
Section: Methodssupporting
confidence: 51%
See 2 more Smart Citations
“…Our FGFR2 SNP, rs2981579, was first identified by Thomas et al [31] and independently replicated in two other GWAS [23, 32]. Other GWAS found stronger associations with other SNPs in the same gene [1, 7, 8, 10, 12, 15, 19, 22, 26]. Ahsan et al [1], for example, reported genome-wide significant p-values for 4 FGFR2 SNPs and young-onset breast cancer, with the smallest p-value seen for rs2981579.…”
Section: Methodssupporting
confidence: 51%
“…Its link to breast cancer is unclear, though there is some evidence that it is a tumor suppressor [66, 67]. Our top hit, rs3803662, was first identified by Easton et al, [7], with several subsequent GWAS confirming the region’s importance [11, 18, 22, 23, 3032]. Presence of this variant allele has been linked to lower TOX3 expression levels in breast tumor tissue [68].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this analysis, we included SNPs reported as genome wide significant (p < 5×10 −8 ) in studies of invasive breast cancer in Caucasian, Asian or Hispanic populations [11,12,15,16,24,17,18,25,10,14,19,26] which we identified by review of the GWAS catalogue [27]. If a SNP was not on the array, we sought a proxy SNP in strong linkage disequilibrium (LD), r 2 > 0.9.…”
Section: Methodsmentioning
confidence: 99%
“…We constructed two separate PRS, one with the allele frequencies and odds ratios (ORs) from Caucasian populations used in the main analysis, and another with allele frequencies and ORs from East Asian populations ( Table S2) [15,16,18]. The Asian-specific PRS had 76 SNPs after the exclusion of SNPs that were non-polymorphic in Asian populations.…”
Section: Methodsmentioning
confidence: 99%